Respuesta :

Answer:

x = -3/2           x=1

Step-by-step explanation:

2x^2+x-1=2

Subtract 2 from each side

2x^2+x-1-2=2-2

2x^2+x-3=0

Factor

(2x   ) (x    )

We will use -3 and 1    or -1 and 3 because we need -3 as the last term

2*1 -3 =-1  wrong we need 1

2 * -1 +3 =1  correct this will give us 1 as the middle term

The -1 goes on the outside and the +3 goes on the inside

(2x +3  ) (x    -1) =0

Using the zero product property

2x+3 =0        x-1=0

2x = -3           x=1

x = -3/2           x=1